HEADING EAST THIS TIME: CRITICAL READINGS ON GENDER IN SOUTHEAST ASIA - Sarmento, Clara (POLISSEMA – Revista de Letras do ISCAP, 2019)
This essay intends to discuss some critical readings of fictional and theoretical texts on gender condition in Southeast Asian countries. Nowadays, many texts about women in Southeast Asia apply concepts of power in unusual areas. Traditional forms of gender hegemony have been replaced by other powerful, if somewhat more covert, forms. We will discuss some universal values concerning conventional female roles as well as the strategies used to recognize women in political fields traditionally characterized by male dominance. Female empowerment will mean different things at different times in history, as a result of culture, local geography and individual circumstances. Empowerment needs to be perceived as an individual attitude, but it also has to be facilitated at the macrolevel by society and the State. Gender is very much at the heart of all these dynamics, strongly related to specificities of historical, cultural, ethnic and class situatedness, requiring an interdisciplinary transnational approach.